1973
DOI: 10.2337/diab.22.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Differential Renal Protein Clearance in Diabetes

Abstract: Measurements of differential renal protein clearance (ratio of the renal clearance of immunoglobulin-G to that of transferrin) have been performed in long-standing diabetics with varying amounts of proteinuria. In seventy-one diabetics the IgC-transferrin clearance ratio (0.44 + 0.04, mean ± S.E.M.) was significantly lower than in seventeen normal subjects (1.85 ± 0.24). The mean IgG-transferrin clearance ratio was significantly lower in fourteen of these diabetics with normal amounts of proteinuria than in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Furthermore, the selectivity index (IgG clearance/transferrin clearance) for Pima diabetics was not significantly different from those of nondiabetic Pimas or Caucasians, a finding which contrasts with an earlier report of significantly decreased IgG/transferrin clearance ratios in diabetics. 33 Among the Pima diabetics, fasting plasma glucose was correlated significantly with total protein excretion, confirming a previous report. 5 However, fasting valves varied significantly among the diabetic groups, being highest among the long-duration diabetics with retinopathy.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the selectivity index (IgG clearance/transferrin clearance) for Pima diabetics was not significantly different from those of nondiabetic Pimas or Caucasians, a finding which contrasts with an earlier report of significantly decreased IgG/transferrin clearance ratios in diabetics. 33 Among the Pima diabetics, fasting plasma glucose was correlated significantly with total protein excretion, confirming a previous report. 5 However, fasting valves varied significantly among the diabetic groups, being highest among the long-duration diabetics with retinopathy.…”
Section: Discussionsupporting
confidence: 87%
“…1 ' 2 Studies of differential renal protein clearances in diabetic patients have demonstrated differences in urinary IgG-transferrin clearance ratios in the early as compared with the late stages of diabetic nephropathy. 41 Studies along these and other lines may help to further elucidate the phenomena reported herein.…”
Section: Discussionmentioning
confidence: 89%
“…Protein excretion has been reported to be increased in some untreated diabetics [5,33,69,70] and to fall with treatment [92], Furthermore, even in diabetics without increased proteinuria, there may be an initial fall in the relative clearance of large plasma protein molecules [61]. An excellent analysis concerning renal protein clearance in diabetics has been published by Jerums etal.…”
Section: Kidney In Diabetes Mellitusmentioning
confidence: 92%
“…An excellent analysis concerning renal protein clearance in diabetics has been published by Jerums etal. [ 61].…”
Section: Kidney In Diabetes Mellitusmentioning
confidence: 99%